(untitled) (Research, Society and Development, 2023)
Noncommunicable Diseases and Injuries (NCDs), including Diabetes Mellitus (DM) and its complications are responsible for more than half of deaths in Brazil, being identified, in 2018, 54.7% of deaths and 11.5 % of deaths from injuries. DM is a pathology of multiple etiologies, resulting from the lack of insulin and/or its inability to exert its effective effects, for glycemic control the patient requires adaptations to the lifestyle. Objective: To describe the coping strategies of DM patients in primary care. Method: This is a quantitative, exploratory, cross-sectional survey study. The research was carried out in a Family Health Strategy (ESF) using questionnaires with sociodemographic information, and the Coping Strategies inventory created by Folkman and Lazarus. Results. In the total of 59 samples, 64.4% are male and 35.6% are female, we found that only 8.5% have type 1 DM and 91.5% have type 2 DM, of the 81.4% of patients have high blood pressure. The coping strategies most used by patients were social support in contrast to the outcome of the confrontation strategy. Conclusion. The results of the study revealed social support among the most relevant coping skills presented, which proved to be an important resource for which primary care is responsible for facilitating this process, and aiming to guarantee the prevention of injuries and maintain the quality of life, stress control is necessary since it is linked to the conditioning of patients.